Pathogenic morphological signatures of perturbations in mitochondrial-related genes revealed by pooled imaging assay - Colin Kremitzki; Jason Waligorski; Graham Bachman; Lina Mohammed Ali; John Bramley; Maria Vakaki; Vinay Chandrasekaran; Purva Patel; Dhruv Mathur; Paul Hime; Robi Mitra; Jeff Milbrandt; et al. (npj Imaging)
Abstract Mutations in mitochondrial-related genes underlie numerous neurodegenerative diseases, yet the significance of most variants remains uncertain concerning disease phenotypes. Several thousand genes have been shown to regulate mitochondria in eukaryotic cells, but which of these genes are necessary for proper mitochondrial function and dynamics? We investigated the degree of morphological disruptions in mitochondrial gene-silenced cells to understand the genetic contribution to the expected mitochondrial phenotype and to identify potentially pathogenic variants like pathogenic mutations in MFN2. We analyzed 5835 gRNAs in a high dimensional phenotypic dataset produced by the image-based pooled analysis platform Raft-Seq. Using the MFN2-mutant cell phenotype, we identified several genes, including TMEM11, TIMM8A, NDUFAF4, NDUFAF7, and NDUFS5 (NADH ubiquinone oxidoreductase-related genes), as crucial for normal mitochondrial dynamics in human U2OS cells. Additionally, we found several missense and UTR variants within the genes SLC25A19 and ATAD3A as drivers of mitochondrial aggregation. By examining multiple features instead of a single readout, this analysis was powered to detect genes which had morphological ‘signatures’ aligned with MFN2-mutant phenotypes. Reanalysis with anomaly detection revealed other critical genes, including APOOL, MCEE, NIT, PHB, and SLC16A7, which perturb mitochondrial network morphology in a manner divergent from MFN2. These studies show causal links between gene knockouts and gene-specific variants into the assembly or maintenance of mitochondrial dynamics and can hopefully lead to a better understanding of mitochondrial related diseases.